Penguatan Kesadaran Hukum Komunitas melalui Sosialisasi Pencegahan Peredaran Narkotika di Desa Penujak, Lombok Tengah, Indonesia - Ahwan, Ahwan; Lalu Panca Tresna D; Muhammad Rifaldi Setiawan; Ayang Afira Anugerahayu; Yuni Ristanti (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
The illegal distribution of narcotics has spread to rural areas. This poses a serious threat not only to the development of the younger generation in villages, but also to the conduciveness and homeostasis of values upheld by rural communities. Responding to growing concerns about this issue, academic intervention in the form of socialization and legal counseling related to the circulation and dangers of narcotics has become an urgent need. This became the basis for the implementation of community service activities with the topic